PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA APOTEK CENTRAL FARMA TAYAN - Sasongko, Agung; Nurmalasari; Iqbal Rizantha, Muhamad; Reza, Mohammad Kamal; Safitri, Sri Dewi Ayu; Meilinda, Eva (LPPM Universitas Bina Sarana Informatika, 2023)
Information systems have become an essential requirement in various aspects of life, including the business world. The presence of an information system can provide benefits in processing organized data and facilitate every process within a system. Pharmacies are one of the businesses in the trading sector that require a data processing system to streamline and improve the performance of their transactions. One example is Apotek Central Farma Tayan Tayan, which currently relies on a manual system. The pharmacy faces challenges such as disorganized drug data and difficulties in tracking incoming and outgoing drugs. Additionally, their reporting process involves manual handwritten records. To address these issues, a research study was conducted with the aim of designing a computerized sales system for Apotek Central Farma Tayan Tayan. The implementation of this system is expected to enhance the pharmacy's performance and effectiveness. The prototype method was employed in this research. The study resulted in the design of an information system accessible to both pharmacists and cashiers. This system facilitates efficient management of drug data, enables the viewing of sales reports, and facilitates the procurement of drugs. Furthermore, the information system securely stores and prints data, ensuring the proper maintenance of vital information within the Pharmacy.